Safety assessment aspects of type B(U) packages containing wet intermediate level waste. (December 2012) - Nehrig, M; Bletzer, C; Wille, F
Abstract : In Germany, the mechanical and thermal safety assessment of approved packages for the transport of RAM is carried out by BAM as the competent authority according to the International Atomic Energy Agency regulations. BAM was involved in several approval procedures with ductile cast iron containers containing wet intermediate level waste. These contents, which are not dried, only drained, consist of saturated ion exchange resin and a small amount of free water. Compared to the safety assessment of packages with dry content, attention must be paid to some more specific points. The physical and chemical compatibility of the content itself and of the content with materials of the package must be shown. From the mechanical resistance point of view, the package has to withstand the forces resulting from the freezing liquid. The most interesting point, however, is the pressure build-up inside the package due to vapourisation. This could be caused by radiolysis of the liquid and must be taken into account for the storage period. The paper deals primarily with the pressure build-up inside the package caused by the regulatory thermal test (30 min at 800°C) as part of the cumulative test scenario under accident conditions of transport. To determine the pressure, the temperature distribution in the content must be calculated for the whole period from the beginning of the thermal test until cooling down. In this case, calculating the temperature distribution requires, besides the consideration of conduction and heat radiation, consideration of evaporation and condensation including the associated processes of transport.